Intergenerational Relationship Between Parental and Their Children’ Gingivitis In Indonesia: A Life Course Approach - Iwany Amalliah Badruddin; Faisha Atiina Maheswari; Febriana Setiawati; Herry Novrinda; Melissa Adiatman (Interdental Jurnal Kedokteran Gigi (IJKG), 2026)
Introduction: Gingivitis, a reversible inflammatory condition, is the second most prevalent oral health issue in children, after dental caries. A national health survey in 2018 revealed a high prevalence of gingivitis among Indonesian children, with 5.8% among 5-year-old and 14.3% among 12-year-old children. Childhood is a critical period for the development of oral health behaviors, which are influenced by genetic, familial, and environmental factors. Research highlights the intergenerational transmission of gingivitis, linking parental oral health to child’s outcomes. This study aimed to analyze the relationship between the occurrence of gingivitis among parents and their 3--14-year-old children in Indonesia. Materials and Methods: Cross-sectional study using secondary data from the 2018 Riskesdas. The data were collected by the Republic of Indonesia Ministry of Health's Research and Development in March 2018. The subject criteria were 3--14-year-old children and their biological parents who had clinical data on gingivitis status and interviews for behavioral variables. Data analysis was performed using SPSS ver.27 for univariate and bivariate analyses. Results and Discussion: The relationship between the occurrence of gingivitis in parents and children was significant (p< .001). The parental risk factors included parents’ perceptions of oral health problems. Parents’ habits were also significantly related to their children’s habits. Conclusion: The significant relationship between the occurrence of gingivitis among parents and children, and the significant role of parents in shaping their children’s oral health behaviors were in accordance with the concept of the intergenerational life course.